2005
DOI: 10.1002/ffj.1495
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the essential oils ofCinnamomum sintoc Blume from a mountain forest of Peninsular Malaysia

Abstract: The leaf, twig, bark and wood oils of Cinnamomum sintoc Blume from a mountain forest of peninsular Malaysia were analysed by GC and GC-MS. Safrole (23.4%) and γ γ γ γ γ-muurolene (13.5%) were the major components of the leaf oil. Other compounds present in appreciable amounts in the oil were eugenol, linalool, terpinen-4-ol, α α α α α-cadinol, germacrene D, α α α α α-terpineol and δ δ δ δ δ-cadinene. The most abundant component of the bark oil was linalool (23.8%). Sesquiterpenes accounted for 25.2% of the oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
15
1
Order By: Relevance
“…The composition of barks sintok oil in this study were significantly different from those reported by Jantan et al [6], which indicated that the linalool was dominant in barks oil (23.8%), followed tetradecanal (16%). Surprisingly, eugenol and their derivatives did not found in bark of sintok Pahang, Malaysia.…”
Section: Chemical Composition Of Essential Oilscontrasting
confidence: 99%
See 2 more Smart Citations
“…The composition of barks sintok oil in this study were significantly different from those reported by Jantan et al [6], which indicated that the linalool was dominant in barks oil (23.8%), followed tetradecanal (16%). Surprisingly, eugenol and their derivatives did not found in bark of sintok Pahang, Malaysia.…”
Section: Chemical Composition Of Essential Oilscontrasting
confidence: 99%
“…terpinen-4-ol (2.4%) and p-cymene (1.3%), the other monoterpenes were present in <1% concentration in the oil [6].…”
Section: Muchtaridi Et Almentioning
confidence: 96%
See 1 more Smart Citation
“…[249] Terpinenes: Hydrocarbons: a-Cadinene; c-cadinene; d-cadinene. [250] Terpinenes: 1,8-Cineole; caryophyllene oxide; germacrene-D; limonene; linalool; myrcene; pcymene; terpinen-4-ol; trans-linalool oxide; a-cadinol; a-humulene; a-terpineol; b-caryophyllene; b-elemene; b-pinene; c-elemene; c-muurolene; c-terpinene [250] Analgesic, [251] anti-inflammatory, [251] antimicrobial, [252] insecticidal, [203] platelet-activating factor (PAF) receptor-binding antagonist activity [39] Abdominal pain, [253] animal bites, [254] diarrhoea, [253] dysentery, [251] fatigue, [115] flatulence, [252] epilepsy, [254] intestinal complaints, [253] insects bite, [253] inflammation, [251] mouth freshener, [253] numbness, [253] pyrexia, [115,252] rheumatism, [254] snake bite, [253] swelling, [254] syphilis, [253] tiredness, [115] ulcer [ [251] Aldehyde: Dodecanal; tetradecanal; undecanal. [250] Fatty acid: Tetradecanoic acid.…”
Section: Leafmentioning
confidence: 99%
“…These compounds are also common to other Lauraceae species, including Cinnamomum, Laurus, Lindera, Ocotea, and Persea genera (Jantan et al 2005;Nor Azah and Jantan 1999;Palazzo et al 2009;Setzer et al 2007). The essential oil of Laurus nobilis leaves contains the nine compounds mentioned before (Kovacevic et al 2007); Laurus azorica has eight of them, lacking caryophyllene oxide (Pedro et al 2001), and Lindera benzoin has seven, lacking linalool and 1,8-cineole (Tucker et al 1994).…”
Section: Discussionmentioning
confidence: 95%